Composite lithium metal electrode manufacturing method, composite lithium metal electrode and lithium metal battery
By using composite lithium metal electrodes with lithium-containing substrates and fluorine-containing inorganic composite layers in lithium metal batteries, the problem of unstable electrodes in traditional lithium metal batteries is solved, and higher battery stability is achieved.
Patent Information
- Application Number
- CN202510230006.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
AI Technical Summary
In traditional lithium metal batteries, due to the active chemical properties of lithium itself, the electrodes are unstable, and more stable lithium metal batteries are needed.
The composite lithium metal electrode is used, including a lithium-containing matrix and a fluorine-containing inorganic composite layer loaded on the surface of the lithium-containing matrix, and the fluorosilicate is formed by mechanical coating.
The composite lithium metal electrode induced uniform deposition of lithium metal through the high lithium metal conductivity and strong lithium philtrum of the fluorine-containing inorganic composite layer, maintained dynamic stability of the electrode surface, prevented the electrolyte from reacting with the lithium-containing electrode, stabilized the electrode sheet interface, thereby improving the stability of the battery.
Smart Images

Figure CN119725811A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium metal batteries, and in particular to a method for manufacturing a composite lithium metal electrode, a composite lithium metal electrode and a lithium metal battery. Background Art
[0002] In recent years, lithium metal batteries have been widely used in various electronic devices such as vehicles and mobile phones. However, due to the active chemical properties of lithium itself, traditional lithium metal batteries can easily lead to unstable electrodes. There is an urgent need to provide lithium metal batteries with higher stability. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide a method for manufacturing a composite lithium metal electrode, a composite lithium metal electrode and a lithium metal battery to solve the problem of electrode instability in the prior art.
[0004] In order to solve the above technical problems, an embodiment of the present application provides a composite lithium metal electrode, comprising a lithium-containing matrix and a fluorine-containing inorganic composite layer supported on the surface of the lithium-containing matrix.
[0005] Preferably, the fluorine-containing inorganic composite layer is made of fluorosilicate by mechanical lamination.
[0006] Preferably, it is characterized in that the fluorosilicate is specifically sodium fluorosilicate or potassium fluorosilicate.
[0007] Preferably, it is characterized in that the thickness of the lithium-containing matrix is 5 micrometers to 2 millimeters.
[0008] Preferably, the material of the lithium-containing matrix includes lithium element or lithium alloy.
[0009] Preferably, the material of the lithium-containing matrix is lithium element; and the thickness of the fluorine-containing inorganic composite layer satisfies the following formula: ; ; in, is the initial porosity of the material of the fluorine-containing inorganic composite layer; is the thickness of the fluorine-containing inorganic composite layer; is the average diameter of the material powder of the fluorine-containing inorganic composite layer; is the preset porosity; is the preset resistance; is the thickness of the lithium-containing matrix; is the cross-sectional area of the lithium-containing matrix; is the electrical conductivity of the material containing the lithium matrix 1; is the electrical conductivity of the material of the fluorine-containing inorganic composite layer.
[0010] In order to solve the above technical problems, the present application also provides a method for preparing a composite lithium metal electrode, comprising: Pressing fluorosilicate onto the surface of a metal lithium sheet to form a fluorine-containing inorganic composite layer, wherein the metal lithium sheet serves as a lithium-containing matrix; The metal lithium sheet coated with fluorosilicate is placed in a processing device for processing and rolled into a composite lithium metal electrode.
[0011] Preferably, the conditions for pressing the fluorosilicate onto the surface of the metal lithium sheet are: under a vacuum environment at room temperature.
[0012] Preferably, the thickness of the fluorosilicate coated on the surface of the metal lithium sheet satisfies the following formula: ; ; in, is the initial porosity of the material of the fluorine-containing inorganic composite layer; is the thickness of the fluorine-containing inorganic composite layer; is the average diameter of the material powder of the fluorine-containing inorganic composite layer; is the preset porosity; is the preset resistance; is the thickness of the lithium-containing matrix; is the cross-sectional area of the lithium-containing matrix; is the electrical conductivity of the material containing the lithium matrix 1; is the electrical conductivity of the material of the fluorine-containing inorganic composite layer.
[0013] In order to solve the above technical problems, an embodiment of the present application provides a lithium metal battery, and the lithium metal battery includes the composite lithium metal electrode provided in the embodiment of the present application.
[0014] The composite lithium metal electrode provided in the embodiment of the present application is used, and the composite lithium metal electrode includes a lithium-containing matrix and a fluorine-containing inorganic composite layer loaded on the surface of the lithium-containing matrix. The fluorine-containing inorganic composite layer has high lithium metal conductivity and strong lithium affinity, can induce uniform deposition of lithium metal, keep the electrode surface dynamically stable, and at the same time prevent the electrolyte from reacting with the lithium-containing electrode, stabilize the electrode interface, and thus can improve the stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the scheme in the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments of the present application. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0016] Figure 1 This is a schematic diagram of the specific structure of a composite lithium metal electrode provided in an embodiment of the present application; Figure 2-1 This is a distribution diagram of the Li element on the surface of a metal lithium sheet provided in an embodiment of the present application; Figure 2-2 This is a distribution diagram of C element on the surface of a metal lithium sheet provided in an embodiment of the present application; Figure 2-3 This is a distribution diagram of the O element on the surface of a metal lithium sheet provided in an embodiment of the present application; Figure 3-1 This is a distribution diagram of the O element on the surface of the composite lithium metal electrode provided in an embodiment of the present application; Figure 3-2 This is a distribution diagram of C element on the surface of a composite lithium metal electrode provided in an embodiment of the present application; Figure 3-3 This is a distribution diagram of F elements on the surface of a composite lithium metal electrode provided in an embodiment of the present application; Figure 3-4 This is a distribution diagram of the P element on the surface of a composite lithium metal electrode provided in an embodiment of the present application; Figure 4 This is a SEM image of the surface of a metal lithium sheet provided in an embodiment of the present application; Figure 5 This is a SEM image of the surface of a composite lithium metal electrode provided in an embodiment of the present application; Figure 6 This is a comparison diagram of cyclic charge and discharge tests between a first lithium metal battery and a second lithium metal battery provided in an embodiment of the present application; Figure 7-1 This is an XPS image of the C element in the composite lithium metal electrode provided in the embodiment of the present application; Figure 7-2 This is an XPS image of the O element in the composite lithium metal electrode provided in an embodiment of the present application; Figure 7-3 This is an XPS image of the Li element in the composite lithium metal electrode provided in the embodiment of the present application; Figure 7-4 This is an XPS image of the F element in the composite lithium metal electrode provided in the embodiment of the present application; Figure 8-1 This is an XPS image of the C element of a lithium metal sheet after a cyclic charge and discharge test, provided in an embodiment of the present application; Figure 8-2 This is an XPS image of the Li element of a metal lithium sheet after a cyclic charge and discharge test, provided in an embodiment of the present application; Figure 8-3 This is an XPS image of the O element of a metal lithium sheet after a cyclic charge and discharge test, provided in an embodiment of the present application; Figure 9-1 This is an XPS image of the C element of the composite lithium metal electrode after cyclic charge and discharge testing provided in an embodiment of the present application; Figure 9-2 This is an XPS image of the O element after the composite lithium metal electrode is subjected to a cyclic charge and discharge test, provided in an embodiment of the present application; Figure 9-3 This is an XPS image of the Li element of the composite lithium metal electrode after a cyclic charge and discharge test, provided in an embodiment of the present application; Figure 9-4 This is an XPS image of the F element of the composite lithium metal electrode after cyclic charge and discharge testing, provided in an embodiment of the present application. DETAILED DESCRIPTION
[0017] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0019] The present application embodiment provides a composite lithium metal electrode, such as Figure 1 The figure shows a schematic diagram of the specific structure of the composite lithium metal electrode, which includes a lithium-containing matrix 1 and a fluorine-containing inorganic composite layer 2, wherein the fluorine-containing inorganic composite layer 2 is loaded on the surface of the lithium-containing matrix 1. Since the fluorine-containing inorganic composite layer has high lithium metal conductivity and strong lithium affinity, it can induce uniform deposition of lithium metal, keep the electrode surface dynamically stable, and prevent the electrolyte from reacting with the lithium-containing electrode, stabilize the electrode interface, and thus improve the stability of the battery.
[0020] The fluorine-containing inorganic composite layer 2 can be made of fluorosilicate by mechanical pressing, wherein the molecular formula of fluorosilicate includes 6 fluorine atoms, so the content of fluorine atoms in fluorosilicate is relatively high, and the fluorosilicate can be specifically sodium fluorosilicate or potassium fluorosilicate. For example, sodium fluorosilicate or potassium fluorosilicate can be uniformly coated on the surface of the lithium-containing substrate 1, and then compacted to obtain the composite lithium metal electrode.
[0021] In the embodiment of the present application, the thickness of the lithium-containing substrate 1 can be 5 microns to 2 millimeters, such as 5 microns, 10 microns, 100 microns, 200 microns, 500 microns, 1 millimeter, 1.5 millimeters, 2 millimeters or other values between 5 microns and 2 millimeters. In addition, the material of the lithium-containing substrate 1 can be lithium, lithium alloy or lithium composite material, wherein the lithium composite material can be, for example, a lithium-boron composite material or a composite material of lithium and other non-metals.
[0022] It should be emphasized that in practical applications, relatively cheap lithium element (i.e., metallic lithium) can usually be used as the material of the lithium-containing matrix 1. For example, metallic lithium sheets can be cut from metallic lithium strips as the lithium-containing matrix 1, and then fluorosilicate is pressed on the surface of the lithium-containing matrix 1. At this time, since the material of the lithium-containing matrix 1 is metallic lithium, and the chemical properties of metallic lithium are relatively active and lithium dendrites are easily generated, the fluorine-containing inorganic composite layer 2 in the present application needs to fully cover the lithium-containing matrix 1 so that the porosity in the fluorine-containing inorganic composite layer 2 is sufficiently low, thereby reducing the possibility of active metallic lithium contacting the electrolyte and reducing the generation of lithium dendrites.
[0023] Therefore, from the perspective of reducing the generation of lithium dendrites, it is usually necessary to set a thicker fluorine-containing inorganic composite layer 2; but on the other hand, the conductivity of the fluorine-containing inorganic composite layer 2 is usually relatively large, and an excessively thick fluorine-containing inorganic composite layer 2 is likely to cause the composite lithium metal electrode itself to have a large resistance, affecting the performance of the lithium metal battery. Therefore, when determining the thickness of the fluorine-containing inorganic composite layer 2, it is usually necessary to comprehensively consider the two aspects of reducing the porosity and the total electrode resistance. In practical applications, the corresponding relationship between the thickness and porosity of the fluorine-containing inorganic composite layer 2 can be approximately simulated, thereby obtaining a calculation formula as shown in Formula 1: Formula 1 In the above formula 1, is the porosity; is the initial porosity, which refers to the ratio of the pore volume to the total volume of the material of the fluorine-containing inorganic composite layer 2 (i.e. the above-mentioned fluorosilicate) in the initial state. is the material parameter of the fluorosilicate, which can be obtained according to actual tests; is the thickness of the fluorine-containing inorganic composite layer 2; is the average diameter of the material powder of the fluorine-containing inorganic composite layer 2 For example, the fluorosilicate powder can be tested for physical properties to determine its average diameter. In other words, the porosity is characterized by the formula The corresponding relationship between the thickness of the fluorine-containing inorganic composite layer 2.
[0024] In this embodiment, the total resistance of the composite lithium metal electrode is simulated to obtain a corresponding relationship formula as shown in Formula 2: Formula 2 In Formula 2, is the simulated total resistance of the composite lithium metal electrode; is the thickness of the lithium-containing substrate 1; is the thickness of the fluorine-containing inorganic composite layer 2; is the cross-sectional area of the lithium-containing matrix 1; is the conductivity of the material of the lithium-containing matrix 1. In this embodiment, the material of the lithium-containing matrix 1 is metallic lithium. is the electrical conductivity of metallic lithium; is the electrical conductivity of the material of the fluorine-containing inorganic composite layer 2, Can be obtained through actual testing.
[0025] After the composite lithium metal electrode is applied to a lithium metal battery, in order to reduce the generation of lithium dendrites, it is obvious that the porosity of the fluorine-containing inorganic composite layer 2 needs to be less than the preset porosity , and the simulated total resistance of the composite lithium metal electrode It also needs to be smaller than the preset resistance , that is, it is necessary to satisfy and , so as to meet the actual application needs.
[0026] Of course, the preset porosity and preset resistor The specific size can usually be determined in combination with specific application scenarios. For example, in scenarios with higher safety requirements, it is more necessary to reduce the generation of lithium dendrites (lithium dendrites are prone to cause internal short circuits). Therefore, the preset porosity The smaller the setting needs to be; in areas where large current is required, it is preferred to set a smaller preset resistance , so the preset porosity can be set according to actual needs and preset resistor The specific size.
[0027] The above is a description of the composite lithium metal electrode provided in the embodiment of the present application, and the method for making the composite lithium metal electrode. For ease of understanding, the method can be further described here in conjunction with a specific example. In this example, the lithium-containing matrix 1 in the composite lithium metal electrode is a lithium single substance (i.e., metallic lithium), and the material of the fluorine-containing inorganic composite layer 2 is sodium fluorosilicate. At this time, a metallic lithium sheet and sodium fluorosilicate powder can be obtained first, and then the sodium fluorosilicate can be pressed on the surface of the metallic lithium sheet. For example, the sodium fluorosilicate can be pressed on the surface of the metallic lithium sheet under a normal temperature vacuum environment. That is to say, at this time, the metallic lithium sheet is used as the lithium-containing matrix, and the sodium fluorosilicate can be pressed on the surface of the metallic lithium sheet under a normal temperature vacuum environment, thereby forming a fluorine-containing inorganic composite layer, and then the metallic lithium sheet after the surface is pressed with sodium fluorosilicate is placed in a processing equipment for processing and rolled into the composite lithium metal electrode.
[0028] The thickness of the sodium fluorosilicate (made into the fluorine-containing inorganic composite layer 2) on the surface of the metal lithium sheet (as the lithium-containing matrix 1) needs to satisfy the following requirements: and .
[0029] In this embodiment, after the composite lithium metal electrode is prepared, the physical properties of the composite lithium metal electrode can be confirmed. For example, as a comparative example, the surface elements of the metal lithium sheet are detected by EDS to obtain the distribution of the surface elements of the metal lithium sheet. Figure 2-1 , 2-2 and 2-3, where Figure 2-1 This is the distribution diagram of Li element on the surface of lithium metal sheet. Figure 2-2 This is the distribution diagram of C element on the surface of lithium metal sheet. Figure 2-3 This is the distribution of O elements on the surface of the metal lithium sheet. Figure 2-1 , 2-2 As can be seen from Figures 2-3, the surface of the metal lithium sheet mainly contains three elements: C, O and Li.
[0030] The surface of the composite lithium metal electrode was tested by EDS, and the following results were obtained: Figure 3-1 , 3-2 , 3-3 and 3-4, where Figure 3-1 is the distribution diagram of O element on the surface of composite lithium metal electrode, Figure 3-2 is the distribution diagram of C element on the surface of composite lithium metal electrode, Figure 3-3 is the distribution diagram of F element on the surface of composite lithium metal electrode, Figure 3-4 : is the distribution diagram of P element on the surface of the composite lithium metal electrode. The element distribution on the surface of the composite lithium metal electrode is shown in Table 1. It can be seen from Table 1 that C, O and F account for the highest proportion, and Na and Si elements are also contained.
[0031] The surface of the metal lithium sheet and the surface of the composite lithium metal electrode were further examined by scanning electron microscopy, and the following results were obtained: Figure 4 SEM images of the surface of the metallic lithium sheet are shown, and Figure 5 The SEM image of the surface of the composite lithium metal electrode shown shows that a fluorine-containing inorganic composite layer 2 made of sodium fluorosilicate is formed on the surface of the composite lithium metal electrode.
[0032] Table 1
[0033] The electrochemical performance was further tested. As a comparative example, a lithium metal sheet was used as the negative electrode and assembled with lithium iron phosphate (as the positive electrode) into a lithium metal battery (referred to as the first lithium metal battery). The lithium metal battery was subjected to a cyclic charge and discharge test at a rate of 1C, wherein the active material loading of the positive electrode was 11.9 mg / cm2. Under the same positive electrode, the composite lithium metal electrode prepared in the embodiment of the present application was replaced with a lithium metal sheet to be assembled into a lithium metal battery (referred to as the second lithium metal battery). The lithium metal battery was subjected to a cyclic charge and discharge test under the same test conditions. The two sets of data were used to make Figure 6 The cycle charge and discharge test comparison chart shown in the figure shows that Figure 6 It can be seen that the capacity retention rate of the second lithium metal battery is still greater than 80% after 450 cycles, while the capacity retention rate of the first lithium metal battery decays to 65% after 100 cycles. It is obvious that the second lithium metal battery has better performance and higher stability.
[0034] In addition, for the composite lithium metal electrode, before testing its electrochemical performance, it can be detected by X-ray photoelectron spectroscopy (XPS) to obtain Figure 7-1 The XPS image of the C element is shown. Figure 7-2 The XPS image of O element is shown. Figure 7-3 The XPS images of Li element and Figure 7-4 XPS image of the F element is shown.
[0035] Furthermore, after the electrochemical performance test, the negative electrode of the first lithium metal battery can also be tested by X-ray photoelectron spectroscopy to obtain Figure 8-1 The XPS image of the C element is shown. Figure 8-2 The XPS images of Li element and Figure 8-3 XPS image of the O element shown; after the electrochemical performance test, the negative electrode of the second lithium metal battery can also be tested by X-ray photoelectron spectroscopy to obtain Figure 9-1 The XPS image of the C element is shown. Figure 9-2 The XPS image of O element is shown. Figure 9-3The XPS images of Li element and Figure 9-4 XPS image of the F element is shown.
[0036] pass Figure 7-1 to Figure 7-4 and Figure 9-1 to Figure 9-4 By comparing the two, it can be found that after the second lithium metal battery was cycled, a CF chemical bond was generated on the surface of the negative electrode, indicating that the fluorine element in the sodium fluorosilicate was well attached to the material, improving the stability of the battery. Figure 8-1 to Figure 8-3 and Figure 9-1 to Figure 9-4 From the comparison, it can be found that the content of Li2CO3 and LiOH is significantly increased, thereby reducing the occurrence of lithium dendrites and improving the stability of the battery, which further indicates that the performance of the second lithium metal battery is significantly better, that is, the performance of the fluorine-containing inorganic composite layer 2 in this application is better.
[0037] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. A composite lithium metal electrode, characterized in that The invention comprises a lithium-containing matrix and a fluorine-containing inorganic composite layer supported on the surface of the lithium-containing matrix; the fluorine-containing inorganic composite layer is made of fluorosilicate by mechanical pressing; the fluorosilicate is specifically sodium fluorosilicate or potassium fluorosilicate.
2. The composite lithium metal electrode according to claim 1, characterized in that The thickness of the lithium-containing matrix is 5 micrometers to 2 millimeters.
3. The composite lithium metal electrode according to claim 1, characterized in that The material of the lithium-containing matrix includes lithium element, lithium alloy or lithium composite material.
4. The composite lithium metal electrode according to claim 3, characterized in that The material of the lithium-containing matrix is specifically lithium element; and the thickness of the fluorine-containing inorganic composite layer satisfies the following formula: ; ; in, is the initial porosity of the material of the fluorine-containing inorganic composite layer; is the thickness of the fluorine-containing inorganic composite layer; is the average diameter of the material powder of the fluorine-containing inorganic composite layer; is the preset porosity; is the preset resistance; is the thickness of the lithium-containing matrix; is the cross-sectional area of the lithium-containing matrix; is the electrical conductivity of the material containing the lithium matrix 1; is the electrical conductivity of the material of the fluorine-containing inorganic composite layer.
5. A method for preparing a composite lithium metal electrode, characterized in that: Pressing fluorosilicate onto the surface of a metal lithium sheet to form a fluorine-containing inorganic composite layer, wherein the metal lithium sheet serves as a lithium-containing matrix; The metal lithium sheet coated with fluorosilicate is placed in a processing device for processing and rolled into a composite lithium metal electrode.
6. The method according to claim 5, characterized in that: The conditions for pressing the fluorosilicate onto the surface of the metal lithium sheet are: under normal temperature and vacuum environment.
7. The manufacturing method according to claim 5, characterized in that: The thickness of the fluorosilicate on the surface of the metal lithium sheet satisfies the following formula: ; ; in, is the initial porosity of the material of the fluorine-containing inorganic composite layer; is the thickness of the fluorine-containing inorganic composite layer; is the average diameter of the material powder of the fluorine-containing inorganic composite layer; is the preset porosity; is the preset resistance; is the thickness of the lithium-containing matrix; is the cross-sectional area of the lithium-containing matrix; is the electrical conductivity of the material containing the lithium matrix 1; is the electrical conductivity of the material of the fluorine-containing inorganic composite layer.
8. A lithium metal battery, characterized in that: The lithium metal battery comprises the composite lithium metal electrode as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Secondary battery and electric device
CN115295765A
Fluorosilicate-coated silicon-based negative electrode material as well as preparation method and application thereof
CN117476913A
Lithium metal fluorination high-entropy SEI layer and preparation method and application thereof
CN117638006A
Method of manufacturing lithium metal anode protectivelayer for lithium battery
KR1020020091748A
Lithium metal negative electrode material, negative electrode sheet, lithium metal secondary battery, electric device, preparation method and use
WO2024221916A1